Academic Reflection – Narratives of Justice and the Welfare State in Times of Austerity - Gedalof, Irene (feminists@law, 2018)
Considers the continuing relevance of chapter 2 of Nicola Lacey's Unspeakable Subjects (1998), on 'Theories of Justice and the Welfare State', to welfare reform within the contemporary neo-liberal state in Britain. Concludes that Lacey’s concern in that chapter, to open ideas of social justice to a recognition of collective differences and to challenge the public/private divide that stabilises and reinforces normative gender, is ever-more urgent in a political moment that refuses precisely these recognitions.